Polemik Bahasa Roh sebagai tanda awal baptisan Roh Kudus - Yanto Sutrisno; Gregorius Suwito; Gidion Gidion (Sekola Tinggi Teologi Sangkakala Jakarta, 2023)
Abstract One of the main factors in church growth is the role of the power of the Holy Spirit in enabling humanity to respond to the preaching of the Gospel. However, to this day, there are still doubts in some church circles about the continuation of the power of the Holy Spirit as happened on the day of Pentecost, especially in the polemic